Analisis SIM Card Cloning Terhadap Algoritma Random Number Generator - Nuril Anwar; Imam Riadi; Ahmad Luthfi (Jurnal Buana Informatika, 2016)
Abstract. Crime in telecommunication sector has increased prevalently, especially with the use of mobile phone which is detrimental both for customers and the providers. In the GSM security system, several weaknesses are found concerning data security outside the network. SIM card clone is part of the security problem in which the data can be transferred to SIM card cloning media. SIM card cloning research can be presented in the form of SRES analysis algorithms A3 and A8 RAND to get Ki Auc for further analysis on SIM card cloning. To test the performance of SIM card cloning, testing parameters such as due under test (DUT) and trial and error are employed. The conclusion of this study is that the SIM card cloning method can occur when Auc Ki is obtained by downloading a crack a8 RAND Random Number Generator analysis algorithms A3 sign SIM card to match the SRES response to the Auc Ki along with supporting data contained in SIM card clones.Keywords: SIM card cloning, Random Number Generator (RAND), Sign Response (SRES).Abstrak. Kejahatan di sektor telekomunikasi kian marak akhir-akhir ini khususnya mobile phone yang merugikan baik bagi customer maupun provider seluler. Pada sistem keamanan GSM, ditemukan beberapa kelemahan di sisi pengamanan data di luar jaringan. SIM card clone adalah bagian dari masalah keamanan pada device SIM card dengan data SIM card yang dapat dipindahkan ke media SIM card cloning. Penelitian SIM Card Cloning ini disajikan berupa analisis algoritma A3 SRES, dan A8 RAND untuk mendapatkan Ki AUc untuk selanjutnya dilakukan analisis SIM Card Cloning. Untuk menguji performa SIM card cloning digunakan parameter pengujian seperti Due Under Test (DUT) dan Trial and Error. Kesimpulan dari penelitian ini didapatkan bahwa metode SIM Card Cloning dapat terjadi bilamana AUc Ki diperoleh dengan melakukan crack A8 Random Number Generator RAND sedang analisis algoritma SIM card dengan mencocokkan A3 Sign Respons SRES terhadap AUc Ki beserta data pendukung yang terdapat pada SIM card hasil kloning. Kata kunci: SIM card cloning, Random Number Generator (RAND), Sign Respons (SRES).